Breast Cancer in West Java: Where Do We Stand and Go? - Yohana Azhar; Hasrayati Agustina; Maman Abdurahman; Dimyati Achmad (National Cancer Center - Dharmais Cancer Hospital, 2020)
Background: Breast cancer is the most common cancer in Indonesia, a low-middle income country in Southeast Asia. We provide a regional hospital-based cancer registry of the central hospital in West Java, Indonesia. This study aims to characterize the presentation, diagnosis, evaluation, and management of breast cancer; to develop a regional breast cancer registry in West Java to monitor cancer care patterns; to evaluate cancer treatment outcomes.Methods: The data were collected from the medical records deposited in the Hasan Sadikin General Hospital Information System. The team has been contracted to operate the registry & organize an advisory board to standardize definitions of coding terminology of the registry’s reporting system and to monitor the cancer care pattern. Data validation was conducted by a team in the cancer registry, consisting of health officers, pathologists, and registrars. Data management and analysis were conducted by the cancer registry team.Results: A total of 913 women diagnosed with breast cancer, from January 2014 until December 2018, were studied. The median age was 49.5 years old. The initial diagnosis was at the age of 42.4 years old on average. About 64.5% were diagnosed with stage-3 and -4 cancers, and 75.1% had undergone a mastectomy, of which 47.3% of the intent was palliative. Of those who have hormonal receptors, only 26.9% were positive, and 36.5% were not assessed for immunohistochemistry evaluation. Inappropriate surgical management of breast cancer was common at the community level, which included indiscriminate diagnostic lumpectomy (21.9%), incomplete mastectomy and omission, or suboptimal lymph node axillary clearance (47.4%). Only 3.0% of patients received breast-conserving surgery and were treated with mastectomy and reconstruction. Conclusions: Breast cancer in West Java is often recognized at the late stage. Treatment was suboptimal, leading to poor survival. A more aggressive approach to early detection and treatment needs to be developed to improve the outcomes of this potentially curable disease.